Paintings about America 1650-1969. (White Plains, N.Y. Center for Humanities, 1971)
Deals with paintings about America by American artists to show the social, intellectual, literary, and economic changes that accompanied the growth of the United States.
Keywords: United States in art; Art, American; Arts; Humanities; Art studies